The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1017/s1751731114002857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tail docking and docking length on neuroanatomical changes in healed tail tips of pigs

Abstract: In pig production, piglets are tail docked at birth in order to prevent tail biting later in life. In order to examine the effects of tail docking and docking length on the formation of neuromas, we used 65 pigs and the following four treatments: intact tails (n = 18); leaving 75% (n = 17); leaving 50% (n = 19); or leaving 25% (n = 11) of the tail length on the pigs. The piglets were docked between day 2 and 4 after birth using a gas-heated apparatus, and were kept under conventional conditions until slaughter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 25 publications
(33 reference statements)
2
29
0
Order By: Relevance
“…In comparison with studies of other painful procedures performed on piglets, tail docking appears to be less acutely painful than piglet castration and similar in painfulness to teeth resection or ear tagging (Marchant-Forde et al, 2009). Identification of neuromas in healed docked pig tails (Herskin et al, 2014) may indicate that docking causes chronic pain, but this has never been investigated (FAWC, 2011).…”
Section: How To Interpret the Results Of The Economic Modellingmentioning
confidence: 99%
“…In comparison with studies of other painful procedures performed on piglets, tail docking appears to be less acutely painful than piglet castration and similar in painfulness to teeth resection or ear tagging (Marchant-Forde et al, 2009). Identification of neuromas in healed docked pig tails (Herskin et al, 2014) may indicate that docking causes chronic pain, but this has never been investigated (FAWC, 2011).…”
Section: How To Interpret the Results Of The Economic Modellingmentioning
confidence: 99%
“…The formation of traumatic neuromas in the stump of tail-docked piglets has been recently described 20, 21 . Both investigations confirmed the presence of traumatic neuromas and neuromatous tissue development in tail stumps collected from pigs of up to 22 weeks of age and suggested that neuroma formation is still incomplete four months after tail docking injury, with possible implications for sensitivity of the tail stump.…”
Section: Discussionmentioning
confidence: 99%
“…Tail lengths were based on recent findings suggesting an effect of the extent of tail resected on the prevalence of neuromas and on neonatal behaviours 20, 54 .…”
Section: Methodsmentioning
confidence: 99%
“…Tail docking has been associated with changes in tail movements and position (18), body posture (19), vocalization (20), and neuroanatomical structures (21) considered to be indicative of pain. Similarly, castration has been linked to changes in behaviors (22, 23) and vocalization considered to be indicative of pain (2426).…”
Section: Introductionmentioning
confidence: 99%